Творцы совпадений: [роман] / Йоав Блум - Блум Йоав (Иностранка, 2020)
Экземпляры: ФИЛ (20210603) / Инвентарный номер: 1114581 / Цена: / Сис.шифр: 84(5Изр) / Авт.знак: Б 70 / ГРНТИ: 17 / ББК: 84(5Изр)-4